Neoadjuvant immune checkpoint inhibitors in high-risk stage III melanoma. Issue 3 (31st May 2022) - Ferraresi, Virginia; Vari, Sabrina
ABSTRACT: The success of immunotherapy and targeted therapy for metastatic melanoma has generated considerable interest in the adjuvant setting, even though high-risk stage III melanoma (with or without in-transit metastases) still holds a substantial probability of relapse, despite surgical resection and available adjuvant treatments. Based on preclinical and clinical trials in resectable melanoma, immune checkpoint inhibitors can enhance anti-tumor immunity by activating antigen-specific T cells found in the primary site. These tumor-reactive T cells continue to exert their anti-tumor effects on remaining neoplastic cells after resection of the primary tumor, potentially preventing relapses from reoccurring. Several trials in the neoadjuvant setting have been conducted for melanoma patients using checkpoint inhibitors with promising early data, showing an improvement of operability and clinical outcomes. Hence, in this study, we review and discuss the available published and ongoing clinical trials to explore the scientific background behind immunotherapy in the neoadjuvant context.